Penyuluhan: Upaya Penguatan Perilaku Anti Korupsi Di Lingkungan SMA Bekasi Di Masa Pandemi Covid-19 - Amalia Syauket; Bambang Karsono; Mic Finanto Ario Bangun (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Corruption has become a real threat to the Indonesianpeople. The impact has been so massive that its eradication mustinvolve all levels of society. Educational institutions, bothuniversities and high schools, take the role of prevention byproviding anti-corruption behavior counseling in the hope ofraising awareness for anti-corruption behavior. This counselingis of group type, namely a group of lecturers as instructors and agroup of students with grades 10, 11 and 12 in several highschools in Bekasi as participants/targets of extension workers,which has been taking place since 2021 and 2022. Conducted bya group of lecturers from Bhayangkara Jaya University asextension officer. The counseling media is carried out onlinebecause of the Covid-19 pandemic, making face-to-face meetingsimpossible, with the adoption stage to be achieved, namely thestudents in the form of efforts to strengthen anti-corruptioneducation in the form of implementing anti-corruption behaviorin their school environment and raising awareness not to commitcorruption. corruption in the family and school environment.Because Anti-Corruption Education has a strategic role inpreventing corruption, it is necessary to strengthen it throughoutreach activities.